(untitled) (Revista Latino-Americana de Enfermagem, 2006)
The study describes changes that are noted in students during training and which contribute to define a professional profile. We carried out a descriptive-exploratory study with a qualitative approach, based on dialectics as a theoretical-methodological framework. The data was obtained from documented analysis and through focal groups with teachers, students and service nurses. The results show the student's position as an active subject in the teaching-learning process, through a movement of transformation of academic structures. A correlation was found between the movement that seeks students' greater political, active and critical participation as a way of determining and guiding the profile of the generalist nurse and greater social insertion. We conclude that, despite efforts, training guidelines and the definition of the professional profile in the study settings is directed at the demands of the labor market, and that competency-based training is still incipient.